KASHKADARYAN INTERPRETATION OF THE EPIC "TAHIR AND ZUHRA" (Scientific journal of the Fergana State University, 2023)
This article deals with another story created by the black section Umirov under the influence of the story "Tohir and Zuhra" composed by Rahmatullah Yusuf oglu. Bakhshi was able to create another version of the story with his creative potential.